HUBUNGAN KUALITAS PELAYANAN (KETERANDALAN, KETANGGAPAN, JAMINAN, EMPATI DAN BUKTI FISIK) TERHADAP PENINGKATAN JUMLAH KUNJUNGAN DI UNIT RAWAT JALAN RUMAH SAKIT UMUM DAERAH ALOEI SABOE KOTA GORONTALO TAHUN 2014 - Mohammad Hadi; Sabirin B. Syukur (program studi ilmu keperawatan fakultas ilmu kesehatan universitas muhammadiyah gorontalo, 2021)
Quality of health care in a hospital is required in order to maintain the number of visits, both curative visit and rehabilitative visit. Good quality service is expected by the patients (customers), it can be a encouragement for the customers to establish strong ties with the service provider such as hospitals, especially, in the globalization era where the competition among health care providers both public and private get stronger ( Kadir, 2002). The purpose of this study was to determine the relationship between the service quality (reliability, responsiveness, assurance, empathy, and physical evidence) and the increase the visit number of outpatient unit at Prof. Dr. Aloei Saboe General Hospital in Gorontalo City. The method used in this research was survey research with an analytical approach. The population was the entire patients of Aloei Saboe Hospital in 2012. The samples were 110 people, taken from all outpatients, by proportional stratified random sampling. There is a relationship between reliability with increased outpatient visits. The test result obtained x2 count (13.838), greater than the x2 table (3,841) phi value of 0.34, whereas the OR value of 6.341, meant that reliability increased 6.3 times the number of outpatient visits. Service responsiveness test results showed that there is a relationship between responsiveness and the increase of outpatient visits. The Service Assurance of Aloei Saboe was lack. The test results showed there is relationship between assurance with the increase of outpatient visits. The test results also showed there is relationship between empathy with the increase of outpatient visit. The test results showed an association between physical evidence with the increased of outpatient visit at Aloei Saboe Hospital.